The Influence of Debt Covenants, Managerial Ownership, Political Costs, and Litigation Risk on Accounting Conservatism - Steviana Roosma; Eliana Eliana; Dhaniel Hutagalung (Yayasan Az Zukhruf Cendikia, 2025)
Objective - This study aims to obtain empirical evidence on the influence of Debt Covenants, Managerial Ownership, Political Costs, and Litigation Risk on Accounting Conservatism. Design/methodology/approach – The quantitative research method uses secondary data. The population in this study is Property & Real Estate companies that publish annual reports audited by independent auditors and sustainability reports listed on the Indonesia Stock Exchange in 2019-2023. Through a purposive sampling method, panel data of 110 observations was obtained. The analytical technique used to test the hypotheses was multiple linear regression analysis using Eviews 9 software. Findings – The results of this study found that Debt Covenants and Managerial Ownership have a positive but statistically insignificant effect on Accounting Conservatism. Political Costs and Litigation Risk have a positive and significant effect on Accounting Conservatism. Research limitations/implications – This study was conducted only on companies in the property and real estate sub-sector listed on the Indonesia Stock Exchange during the period 2019–2023, This research only used sources from the companies’ financial statements and sustainability reports.